High‐risk Stage III colon cancer patients identified by a novel five‐gene mutational signature are characterized by upregulation of IL‐23A and gut bacterial translocation of the tumor microenvironment. Issue 7 (27th November 2019) - Ge, Weiting; Hu, Hanguang; Cai, Wen; Xu, Jinhong; Hu, Wangxiong; Weng, Xingyue; Qin, Xin; Huang, Yanqin; Han, Weidong; Hu, Yeting; Yu, Jiekai; Zhang, Wufeng; et al.
Abstract : The heterogeneities of colorectal cancer (CRC) lead to staging inadequately of patients' prognosis. Here, we performed a prognostic analysis based on the tumor mutational profile and explored the characteristics of the high‐risk tumors. We sequenced 338 colorectal carcinomas as the training dataset, constructed a novel five‐gene ( SMAD4, MUC16, COL6A3, FLG and LRP1B ) prognostic signature, and validated it in an independent dataset from The Cancer Genome Atlas (TCGA). Kaplan–Meier and Cox regression analyses confirmed that the five‐gene signature is an independent predictor of recurrence and prognosis in patients with Stage III colon cancer. The mutant signature translated to an increased risk of death (hazard ratio = 2.45, 95% confidence interval = 1.15–5.22, p = 0.016 in our dataset; hazard ratio = 4.78, 95% confidence interval = 1.33–17.16, p = 0.008 in TCGA dataset). RNA and bacterial 16S rRNA sequencing of high‐risk tumors indicated that mutations of the five‐gene signature may lead to intestinal barrier integrity, translocation of gut bacteria and deregulation of immune response and extracellular related genes. The high‐risk tumors overexpressed IL23A and IL1RN genes and enriched with cancer‐related bacteria ( Bacteroides fragilis, Peptostreptococcus, Parvimonas, Alloprevotella and Gemella ) compared to the low‐risk tumors. The signature identified the high‐risk group characterized by gut bacterial translocation and upregulation of interleukins of the tumor microenvironment, which was worth further researching. Abstract : What's new? The heterogeneity of colorectal cancer makes it difficult to determine patients with a poor prognosis or in need of advanced therapy. Here, the authors constructed and validated a novel 5‐gene ( SMAD4, MUC16, COL6A3, FLG, and LRP1B ) mutational prognostic signature to identify high‐risk patients with Stage III colon cancer. Mutations of these five genes may lead to loss of intestinal barrier integrity, translocation of gut bacteria, and deregulation of interleukins and extracellular‐related genes. Combining tumor genetic characteristics with dynamic tumor microenvironment changes may lead to more promising prognostic signatures, which could help better select cancer patients for systemic therapy after surgery.